Mandatory Nutritional Labeling and Implications for Indian Food Companies - Intodia, Vijay (Indian Journal of Marketing, 2011)
Nutritional labeling has been made mandatory in India for all the processed food products. Government intervention is aimed at achieving the social goals as improved health status for the people and streamlining the country’s regulatory environment with the international requirements. Economic literature suggests that mandatory labeling helps in reducing the problems of asymmetric information, which improves the market efficiency. Consumers will be benefited in terms of availability of nutritional information, which enables them in making informed choices about the food products. Product reformulation is another benefit of the regulation, as companies would prefer reformulating the product rather than losing sales due to disclosure of negative product characteristics. At the same time, the regulation would result in cost implications for the food companies, particularly companies in the small sector. Therefore, it is pertinent that the Government provide continued support to food companies in terms of technical and financial assistance. Besides clear guidelines, testing facilities and enforcement mechanism are some of the critical factors for the successful implementation of the regulation. Food companies may also increase their profitability by developing differentiated food products based on specific nutrient characteristics. The regulation would only help food companies to be competitive in the global markets.